APLIKASI PROXIMITY BEACON SEBAGAI SENSOR ANTI TABRAKAN MENGGUNAKAN MICROBIT UNTUK PEMBELAJARAN PEMROGRAMAN SISWA-SISWI SMP DI SEKOLAH HAMIDAH SAMPURNA, KABUPATEN BANDUNG - Novamizanti, Ledya; Iwut Tritoasmoro, Iwan; Fardan, Fardan; Danny Adviatmadja, Sebastian; Imansyah Basudewa , Muhammad; Aqilah Mamur Tanjung , Najmi (Universitas Mataram, 2025)
The development of digital technology requires the young generation to have technological literacy and programming skills from an early age. To answer this challenge, the community service team from the Electrical Engineering Faculty of Telkom University carried out activities at Hamidah Sampurna Junior High School (SHS), Bandung Regency. This activity has the theme